2013
DOI: 10.4236/ojps.2013.34023
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Fraud in Nigeria: A Philosophical Evaluation of the Framework of Electoral Violence

Abstract: In the 2011 general elections in Nigeria, the Independent National Election Commission (INEC), the electoral management body (EMB) that organized the elections pulled what may pass as an electoral feat in achieving one of the most open, credible, peaceful and transparent elections within Nigeria's recent memory. Before the 2011 elections, Nigeria had the 1999, 2003 and the 2007 elections considered by both national and international election observers, the Common Wealth Election Monitoring groups and the civil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Since the return to democratic rule, human rights abuses have remained widespread and protests against political corruption and police brutality have been repressed violently by the government (Uwazuruike, 2022). Furthermore, elections have been characterized by fraud and political violence (Aluaigba, 2016; Casimir et al, 2013), both of which can discourage widespread participation. Voting trends show that turnout in Nigeria has decreased steadily over the past two decades, from 69% in the 2003 election to less than 29% in 2023 (Clowes, 2023), possibly indicating disillusionment with democracy and disengagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the return to democratic rule, human rights abuses have remained widespread and protests against political corruption and police brutality have been repressed violently by the government (Uwazuruike, 2022). Furthermore, elections have been characterized by fraud and political violence (Aluaigba, 2016; Casimir et al, 2013), both of which can discourage widespread participation. Voting trends show that turnout in Nigeria has decreased steadily over the past two decades, from 69% in the 2003 election to less than 29% in 2023 (Clowes, 2023), possibly indicating disillusionment with democracy and disengagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clearly, the campaign strategies adopted by political parties often involve cash and material inducements to influence voters to vote for a political party or its candidate during elections (Yakubu, 2020). Vote buying influences the political behaviours of both the politicians and the electorates with negative impacts on the credibility of the electoral process and the civic right of the voters (Casimir et al, 2013;Onwe et al, 2015;Suleiman, 2016;Chukwurah et al, 2019). Although, a study conducted by Muhtadi (2019) observed that vote buying influences the voting behaviour of 10% of the respondents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various scholars (Tar & Zak-Williams, 2007;Human Rights Watch, 2007;Casimir et al 2013;Bariledum et al 2016;Isma'ila & Othman, 2016;Ozoemena &Evangelina, 2019 andDada, 2021) believed that electoral fraud is committed in Nigeria through multiple stages and processes leading to challenges of legitimacy and good governance. Apart from challenges of good governance, electoral fraud in Nigeria is accompanied with protests in disagreement and legitimacy question (Daxecker et al 2019).…”
Section: The Concept Of Electoral Fraudmentioning
confidence: 99%